A comparative study of pentanol (C5 alcohol) and kerosene blends in terms of gas turbine engine performance and exhaust gas emission. (15th February 2023) - Suchocki, T.; Kazimierski, P.; Lampart, P.; Januszewicz, K.; Białecki, T.; Gawron, B.; Janicka, A.
Highlights: Gas turbine performance of JET A/pentanol blends were investigated. Engine efficiency decreases when alcohol is used. Increasing the fraction of pentanol in the mixture leads to a lower EGT. JET A/alcohol blends show fewer NOx, and CO emissions. Abstract: The growing demand for sustainable and clean energy sources provides the incentive for the development of alternative fuels. Simultaneously, the development of gas turbine technologies with flexible fuel supply systems enables the use of alternative non-fossil fuels that can play key roles in contributing to global efforts in meeting emissions targets. This paper presents the current state of knowledge on the production and potential use of pentanol (C5 alcohol) in diesel engines and gas turbines. The combustion performance of a GTM-140 jet engine supplied by mixtures of pentanol with aviation kerosene is then evaluated and the results are compared with those of kerosene mixtures with other biofuels – propanol (C3 alcohol)) and butanol (C4 alcohol)). All the investigated liquid biofuel alternatives showed potential for reducing regulated emissions such as NOX (on average by 40%) and CO (on average by 25%) for C5 alcohol. The increase in the proportion of pentanol in the blends has the effect of reducing the temperature downstream of the combustion chamber on average by 5.8% for Turbine Inlet Temperature (TIT) and 6.1% for Exhaust Gas Temperature (EGT). The jet engine fuel efficiency expressed as thrust specific fuel consumption (TSFC) for all tested biofuels decreased on average by 40% for C5 alcohol. The use of alternative fuels such as bio-alcohols offers real opportunities for cleaner and more environmentally friendly gas turbine operation in aviation and power generation.